2014
DOI: 10.18553/jmcp.2014.20.4.376
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Use of Amiodarone Influences Warfarin Maintenance Dose but Is Not Associated with Adverse Events

Abstract: BACKGROUND: Drug interaction studies selecting patients in a real-life setting are scarce, and most studies to date are characterized by a small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In the same study, co-medication with carbamazepine warranted a massive 40% increase in the dispensed dose of warfarin because of the CYP2C9 enzyme-inducing effect of carbamazepine. In a more recent study by Santos et al [67], 111 (12.8%) of the 866 patients maintained on warfarin were concurrently taking amiodarone, and the maintenance dose of warfarin was significantly lower (by 19.6%) in these patients compared with the 755 who were not on amiodarone. The frequency of patients whose international normalized ratio (INR) was within the therapeutic range was 51.4% in the users and 60.5% in the non-users of amiodarone.…”
Section: Genotype-dependent Susceptibility To Phenoconversionmentioning
confidence: 89%
“…In the same study, co-medication with carbamazepine warranted a massive 40% increase in the dispensed dose of warfarin because of the CYP2C9 enzyme-inducing effect of carbamazepine. In a more recent study by Santos et al [67], 111 (12.8%) of the 866 patients maintained on warfarin were concurrently taking amiodarone, and the maintenance dose of warfarin was significantly lower (by 19.6%) in these patients compared with the 755 who were not on amiodarone. The frequency of patients whose international normalized ratio (INR) was within the therapeutic range was 51.4% in the users and 60.5% in the non-users of amiodarone.…”
Section: Genotype-dependent Susceptibility To Phenoconversionmentioning
confidence: 89%
“…Our results partially corroborate recent evidence on drug–drug interactions (DDIs). Santos et al [42] showed that simultaneous use of warfarin and amiodarone was not associated with adverse events in chronic OAC therapy. Also, a previous study [43] found that the combination of single antiplatelet therapy with an anticoagulant was associated with a significantly greater risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…A drug-drug interaction of amiodarone with VKAs is also well-known. VKA maintenance dose is lower in patients simultaneously using amiodarone compared with patients without amiodarone, and patients taking amiodarone have higher INR/current dose ratios compared with patients not using amiodarone [18]. It is uncertain, however, to which degree amiodarone affects the anticoagulant effects of rivaroxaban [19].…”
Section: Discussionmentioning
confidence: 99%